Study on Oil Flow Characteristics and Winding Temperature Distribution of Oil-immersed Transformer - Chen, Ye; Luo, Chuan; Xu, Wenjiao; Zhang, Guipeng; Tang, Biao; Wei, Ling; Zhao, Zhengang (Distributed Generation & Alternative Energy Journal, 2021)
The stability and effective functioning of a power grid depend upon the reliability as well as safety prospects of a transformer which is the principal component of the power system. The natural oil circulation in the oilimmersed transformer drifts the oil flow by the change in the density which is again caused by the change in temperature. But the pressure is comparatively low with respect to the oil pump causing the lower down of velocity which in turn dissipates unimpressionable heat. In this paper, a noble attempt has been made to build a natural oil circulation layer-type winding transformer based on a fluid-solid coupling heat transfer model pertaining to the internal temperature field and flow field by using the fluid mechanics’ simulation software. In the next stage, the authors have analyzed the temperature distribution, hot spot, position condition of the variable winding, the horizontal the oil channel width as well as the temperature of the winding transformer. The paper is of great significance as it examines the influence of the flow characteristics of oil channel on the winding temperature distribution. The outcome can significantly improve the structure of heat dissipation and the operating environment of the transformer.